Improving skills of farmers and development agents on integrated pest and disease management on food legumes in Ethiopia and Lebanon - Kassaw, Admasie; Choueiri, Elia; Abtie, Abate; Assaye, Gebremariam; El Amil, Rola; Abathun, Tamir; Kumari, Safaa; Moukahel, Abdulrahman; Alem, Cherinet; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2023)
Summer and winter crops (cereals, vegetables and food legumes) are suffering from attacks of insect pests, parasitic weeds and diseases in Ethiopia and Lebanon. The damage is both in quality (Figure 1) and quantity affecting food security and incomes of farmers. Farmers and development agents’ skills and knowledge gaps hinder proper management of new and emerging pests and diseases in both countries. Training of male and female farmers and village level extension staff was given on the management of insect pests and diseases to improve their skills and knowledge. Farmer participants for the training in the PHI intervention sites were identified by village level extension staff based uisng key criteria like educational background, devotion, initiatives, age, and gender.